Methodology of Economic Evaluation of Balneological (Spa) Resorts of Russian Federation - Victoria V. Prokhorova (International Journal of Economics and Financial Issues, 2016)
The problem of economic efficiency of Russian spa resorts is the cornerstone. Any business entity tends to benefit (economic effect) on its activities. For large amounts of an economic entity such as an enterprise or an entire state, counting benefits may be relatively time-consuming process, compared with the smaller entities, for example, such as a separate individual. In such circumstances, there is a need to find ways of comprehensive methodology for assessing the cost-effectiveness of spa resorts in Russia. The most important place in the health care system belongs to the resorts of Russians using the preventive, curative and rehabilitative purposes of the unique natural factors that provide versatility and high efficiency of rehabilitation treatment and rehabilitation of basic social diseases. In Russia, spa tourism - is not new, since at all times a favorite place of rest of Russians were the southern resorts of the Caucasian Mineral Waters, the head of which, of course, Essentuki, Zheleznovodsk, Kislovodsk and Pyatigorsk. The uniqueness of these cities is that they are located in the most convenient places: on the one hand, this is the best spa resorts in Russia, and on the other - the nature of these places she performs a very important and powerful factor contributing to the improvement of the body.